Scope and limitations of teleconsultation during the covid-19 pandemic: accounts from primary healthcare professionals in the Autonomous City of Buenos Aires - María de las Nieves Ganiele; Mariela Alejandra Weisbrot; Andrea Melissa Sian; Julieta Milagros Carosella Reboredo; María Victoria Weisbrot; María Florencia Grande Ratti (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2024)
The aim was to explore the scope and limitations of teleconsultation during the pandemic from the perspective of primary care physicians at the Hospital Italiano de Buenos Aires, a private institution located in the Autonomous City of Buenos Aires. A qualitative study was conducted with ten individual semi-structured interviews between January and April 2022. The three major emerging topics were the transition to virtuality, accessibility, and the new care model. Obstacles were related to the massive, forced, and unplanned implementation of teleconsultations. The main benefits included providing care during isolation-distancing and addressing epidemiological doubts. Changes were highlighted in care strategies, consultation frameworks, exchange among colleagues, referral criteria, requests for complementary studies, and in the profiles of those seeking consultations. A misuse of the system by individuals and a trivialization of the consultation moment emerged. The rise of communication and information technologies undoubtedly allowed the continuity of healthcare processes, but it does not replace in-person care, and normative guidelines are needed for its continuity.